PENGEMBANGAN WIRAUSAHA PRODUK FISH JELLY IKAN BANDENG DI POLITEKNIK PERTANIAN NEGERI PANGKEP - Fitri, Muhammad; Arfini, Fifi; Laylah, Nur (Jurnal Dinamika Pengabdian, 2018)
Development of marketing of Fish Jelly Product entrepreneurship in State Pangkep Agriculture Polytechnic is expected to improve socio-economic aspect for people of South Sulawesi, especially Pangkep regency and provide nutritional needs and diversification of processed milkfish products and if cultivated maximally will increase people's income. The purpose of entrepreneurship development of Fish Jelly Products is to develop an entrepreneurial culture and provide work experience to students and alumni in college. The entrepreneurship  marketing development program of fish jelly production (meatballs, nuggets, brains, dragon legs, sausage and tofu) of milkfish in the year 2017 activity produced as much as 3240 kg (weighs 500 gr / pack) with production / year of 6480 packages sold IDR 20,000 per package resulted in a total sale of IDR. 129.6 million. The marketing of Fish Jelly product was carried out through Mini Plant State Agricultural Polytechnic of Pangkep, minimarket of Pangkep, Barru, Maros and Makassar municipalities as well as on line system sales. Keywords: Surimi, Milkfish, Fish Jelly, Development, Entrepreneurship